Analysing roles of position in curling based on shot-scores - Hirata, K.; Masui, F.; Ohtani, H.; Yanagi, H.; Ptaszynski, M. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This paper reports on the analysis of the characteristics for each position based on shot-scores in curling. We computed average shot-scores for each position from 26 curling game information, and analyzed the correlation between the differences in average shot-scores and the differences in final game scores. The results show that strong correlations appeared for the position of the lead and the fourth, and weak correlations for the second and the third. It indicates that the roles of the lead and the fourth relate to game score directly, but the roles of the second and the third relate to the game progress. We were able to confirm the relationship between the score and each position of the target team.